2012
DOI: 10.1371/journal.pone.0029834
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Timing, Duration, and Symmetry of Molt of Hawaiian Forest Birds

Abstract: Food limitation greatly affects bird breeding performance, but the effect of nutritive stress on molt has barely been investigated outside of laboratory settings. Here we show changes in molting patterns for an entire native Hawaiian bird community at 1650–1900 m elevation on the Island of Hawaii between 1989–1999 and 2000–2006, associated with severe food limitation throughout the year beginning in 2000. Young birds and adults of all species took longer to complete their molt, including months never or rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 49 publications
2
52
0
2
Order By: Relevance
“…In the same study, primary-feather asymmetry decreased as the amount of subcutaneous fat stored during molt increased. In a nonexperimental study, the causal effect of food limitation on molt asymmetry was demonstrated for a group of Hawaiian forest avian species (Freed and Cann 2012). It was also found that Common Whitethroats (Sylvia communis) starting molt late in the season showed a higher degree of asymmetry in feather replacement than early-molting individuals (Hall and Fransson 2001), and the authors suggested that this pattern could be attributed to high metabolic rate caused by the stress of molting late in the year.…”
Section: Discussionmentioning
confidence: 94%
“…In the same study, primary-feather asymmetry decreased as the amount of subcutaneous fat stored during molt increased. In a nonexperimental study, the causal effect of food limitation on molt asymmetry was demonstrated for a group of Hawaiian forest avian species (Freed and Cann 2012). It was also found that Common Whitethroats (Sylvia communis) starting molt late in the season showed a higher degree of asymmetry in feather replacement than early-molting individuals (Hall and Fransson 2001), and the authors suggested that this pattern could be attributed to high metabolic rate caused by the stress of molting late in the year.…”
Section: Discussionmentioning
confidence: 94%
“…During 2005, prevalence of non-normal molt was lowest in the closed forest site, but became highest in 2006 (Freed and Cann 2012). This reversal was associated with increased density of white-eyes in the closed forest area and decreased density in the open forest area between 2005 and 2006 (Fig.…”
Section: Speciesmentioning
confidence: 90%
“…Changes included lower mass, lower fat, shorter legs, and shorter bills (Freed et al 2008a,b;, which generated lower juvenile and adult survival. In addition, we identified changes in timing, duration, and symmetry of molt of all native species, with increasingly lower survival during the winter months of 2000(Freed and Cann 2012. These changes in molt have been experimentally induced by severe food limitation in other birds (Murphy et al 1988, Swaddle andWitter 1994).…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Frog muscle tissue turns over roughly 60-80 days (Cloyed et al 2015), Hawaiian bird feather molt takes about 90-120 days (Freed and Cann 2012), and bat wing membrane tissue turnover is about 50 days (Roswag et al 2015). Because the turnover rates for all these tissues are within 2-6 months, we felt that all samples collected for isotope analyses reflected the resource base for that year and should be comparable.…”
Section: Sample Collectionmentioning
confidence: 99%